Comparative study of some symmetric ciphers in mobile systems - Jassim, Khalid Fadhil; Alshaikhli, Imad Fakhri Taha (2014)
Nowadays, the use of mobile communication systems are growing increasingly across the world, huge sensitive information exchanging over these systems. The security problems of information confidentiality, authenticity, and integrity became a prime concern of issue for users and society. Symmetric cryptographic algorithms have been proposed to protect the information of the senders and receivers through mobile systems. There are various symmetric cryptographic algorithms such as KASUMI cipher, SNOW cipher, ZUC cipher, and AES cipher have been developed for achieving secure mobile communication systems. Some cryptanalysis techniques (e.g. Sandwich Cryptanalysis Technique, Sliding Property Technique, Differential Cryptanalysis Technique, and Biclique Cryptanalysis Technique) can be used to attack these symmetric ciphers, therefore there is a need for more analysis studies to address the security problems of these ciphers. This paper presents a comparative study of these symmetric ciphers with focus on analysis of their specifications, components, and some cryptanalysis techniques over each other